2013
DOI: 10.1007/s10840-013-9817-3
|View full text |Cite
|
Sign up to set email alerts
|

Deep sedation during catheter ablation for atrial fibrillation in elderly patients

Abstract: Deep sedation with propofol and midazolam during AF ablation did not result in an increased rate in sedation-related complications in elderly patients. Similarly, the rate of procedural complications was not significantly different among the study groups. The rate of respiratory infections and renal failure was significantly higher in the elderly. All adverse events were treated successfully without any remaining sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Although some studies have reported hypotension as a side effect of deep sedation during AF ablation, it is not prolonged and usually controllable [23]. In the present study, the sedation level was appropriate, and no patients required inotropic drugs for severe hemodynamic instability.…”
Section: Discussionmentioning
confidence: 54%
“…Although some studies have reported hypotension as a side effect of deep sedation during AF ablation, it is not prolonged and usually controllable [23]. In the present study, the sedation level was appropriate, and no patients required inotropic drugs for severe hemodynamic instability.…”
Section: Discussionmentioning
confidence: 54%
“…Guiot et al demonstrated that age >75 years is an independent predictor of late cerebrovascular events . Wutzler et al reported that respiratory infections and renal failure after ablation are high in the elderly . However, several trials investigating the complication rates in elderly patients undergoing ablation have shown favorable outcomes as compared to those in younger patients .…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining sedation in cardiac EP have focused on safety and feasibility, assessing complications associated with anesthesia and ablation‐related complications . Deep sedation under propofol has been shown to be safe even in elderly patients . Procedural sedation with ketamine is also reported in the field of EP .…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13] Deep sedation under propofol has been shown to be safe [12][13][14] even in elderly patients. 15 Procedural sedation with ketamine is also reported in the field of EP. 16 However, very few data are available on patients' satisfaction with sedation for catheter ablation, whereas after gastroenterologic endoscopic procedures under deep sedation patients expressed a high level of satisfaction.…”
Section: Discussionmentioning
confidence: 99%